'Eyesight to the Blind': Secular and Religious Dialogue in the 'Devil's Music'. Issue 4 (16th November 2022) - Curtis, Bruce
Abstract: I adopt a dialogic approach to refute Paul Oliver's claim that there is no challenge to the authority of the black Church or religion in the segregated 'race records' of the first half of the 20th century in the United States. I dismiss the claims of some black theologians that the presence of biblical imagery in the blues means that performers were essentially religious. I show that the dialogue between secular song and religious sermons on record involved mutual parody, satire, and polemic in a common speech genre. Attacks on the Church, its members, clergy, and doctrines were common. Recorded sermons spoke back in defense. Mikhail Bakhtin's concepts offer purchase on the relations between secular and religious recordings in an ongoing struggle for hegemony in black cultural production.